Perdebatan Kebijakan Penggunaan Seragam Sekolah di Era Merdeka Belajar - Suteki, Mega; Sulistyowati, Retno Wuri; Saputro, Eko Edi (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2024)
The use of school uniform has a long history in Indonesian education system since the Dutch colonial era. This article discusses various stakeholders’ perspective on the policy of school uniform, wheter it has positive or negative impact on students. This study uses a qualitative descriptive approach with a semi-structured interview method to describe various stakeholders’ perspective regarding the usage of school uniforms in educational institutions.  The participants of this study are principals, students, teachers, and guardians. This paper describes different views between those who believe that school uniforms bring a positive impact on students and those who oppose the use of school uniforms and considered its usage will limit the pupil’s freedom of learning. The advocate of school uniforms belive that school uniforms can instill discipline, a sense of nationalism, reduce visible social inequalities, and reduce the risk of violence. While the opponents of the school uniform policy consider that school uniforms' usage limit pupil’s freedom of learning, and reduce their chance to learn about tolerance, and increases the risk of conflict between schools.